Study protocol of a phase 1 clinical trial establishing the safety of intrapleural administration of liposomal curcumin: curcumin as a palliative treatment for malignant pleural effusion (IPAL-MPE) - Hocking, Ashleigh Jean (BMJ Open, 2021)
INTRODUCTION: This is a phase 1, open-label, single-centre, uncontrolled, dose-escalation study to evaluate the feasibility, tolerability and pharmacokinetic profiles of a single dose of liposomal curcumin, administered via an existing tunnelled indwelling pleural catheter (TIPC) directly to the tumour site in individuals with diagnoses of malignant pleural effusion. Primarily, we aim to determine a maximum tolerated dose of liposomal curcumin administered via this method. METHODS AND ANALYSIS: We will use a 3+3 expanded cohort for predefined dose-escalation levels or until a predefined number of dose-limiting toxicities are reached. Participants will be administered a single dose of liposomal curcumin (LipoCurc, SignPath Pharma) via their existing TIPC as a sequential enrolling case series with the following dose cohorts: 100, 200 and 300 mg/m(2). Primary endpoints are determination of the maximum tolerated dose within the predetermined dose range, and determination of the feasibility of intrapleural administration of liposomal curcumin via an existing TIPC. Secondary endpoints include determination of the safety and tolerability of intrapleural administration of liposomal curcumin, median overall survival, effects on quality of life and on feelings of breathlessness, and the pharmacokinetics and concentrations of curcumin from the plasma and the pleural fluid. Important inclusion criteria include age ≥18 years, an existing TIPC, a pleural biopsy or pleural fluid cytology-proven diagnosis of malignant pleural effusion and for whom no antitumour therapy of proven benefit is available or has been previously declined, eastern cooperative group performance status <2. ETHICS AND DISSEMINATION: The study protocol has been approved by the Southern Adelaide Local Health Network Human Research Ethics Committee (HREC) (approval number: HREC/20/SAC/11). Study results will be published in peer-reviewed journals, and presented at conferences, in field of medical oncology and respiratory medicine. TRIAL REGISTRATION NUMBER: ACTRN12620001216909. PROTOCOL VERSION NUMBER: V.1.0.